Mapping Databases To Ontologies To Design And Maintain Data In A Semantic Web Environment - Olivier Curé (Journal of Systemics, Cybernetics and Informatics, 2006)

(untitled)
This paper presents a global framework which enables the end- user to design, enrich and maintain an ontology from an existing database. These functionalities facilitate the development and maintenance of Semantic Web applications from frequently updated and domain- concerned databases. The efficiency of this framework is evaluated through the study of a medicine - oriented Semantic Web application which benefits from all the features of the DBOM framework.